Dermatologists' perspectives on healthcare of patients with atopic dermatitis: A cross‐sectional study in Germany. Issue 1 (22nd November 2022) - Tizek, Linda; Tizek, Lucas; Schneider, Simon; Wecker, Hannah; Biedermann, Tilo; Zink, Alexander
Abstract: Background: Atopic dermatitis (AD) is a common chronic skin disease causing substantial individual and overall socioeconomic burden. Objectives: The aim of this study was to gain information on the healthcare of patients with AD from dermatologists' perspectives. Methods: For this cross‐sectional study, office‐based dermatologists in Southern Germany were contacted by mail in June 2021, who received a questionnaire that assessed, for example, individual data, annual number of patients, treatment satisfaction, and awareness of patients' online searches. Results: The 98 participating dermatologists (mean age 53.2 ± 10.3 years, 53.1% male) reported treating a median of 300 patients with AD yearly, of those 11.0% had a severe form. Two‐thirds of physicians were consulted at least six times a year by severely affected patients. Many physicians were contacted by several patients who were pretreated by other physicians. Topical corticosteroids were the most frequently used therapy. The median proportion of patients receiving a biological was 2.0%. While nearly all dermatologists (89.8%) were satisfied with the effectiveness of available therapies, only 37.7% were satisfied with their costs. Concerning perceived treatment satisfaction among patients, 65.3% of patients with severe AD seemed satisfied. Patient use of the internet for health information was indicated to be beneficial for the awareness of AD by 74.5% of physicians, whereas most found it obstructive to patients' claims (69.1%) and therapy decisions (48.4%). Nearly the same proportion mentioned that online searches were an obstacle for (37.9%) or had no effect on (38.9%) the physician–patient relationship. Conclusions: The results indicated that care of AD, especially in severely affected people, can still be improved. Additionally, from the dermatologists' perspectives, online searches mostly have a negative effect on several healthcare‐related aspects.